Avaliação de genotoxicidade em peixes de duas áreas portuárias do Rio Tapajós, no Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The port zone are essentials to the socioeconomic development of the Amazon region, however, it can contributes to disturbing aquatic ecosystems by the intensive shipment drive and occasional discharge of pollutants. Among the chemical species that are harmful to the environment and associated with the port activities stand out the heavy metals and petroleum derivatives. Such xenobiotic molecules induces genotoxic damages to aquatic biota. The present study aims to investigate the possible genotoxic effects in fishes Pimelodus blochii and Geophagus proximus in situ exposed to aquatic pollutants in the port zones of Santarém and Itaituba cities, situated in the Tapajós Rivers, western Pará State. Therefore were collected 60 fishes, G. proximus (n=39) and P. blochii (n=21) from the both localities. The micronucleus test and counts of erithrocyte nuclear abnormalities were adopted for detection of genetic material losses and nuclear membrane lesions, while the comet assays was applied to evaluate DNA damages. P. blochii from the Itaituba port zone showed larger index of damage to DNA, while G. proximus from Santarém showed greater frequencies of micronucleus and nuclear abnormalities. A comparison between both species revealed that G. proximus is more susceptible to the xenobiotics found in the study area. The last increasing in the port sector in the Tapajós system may be associated with the high level of genotoxic damages observed in fishes from the Santarém area. On the other hand, the prolonged exposition to mining residuals and urban garbage could explain the high level of DNA damage observed in P. blochii from the Itaituba area. Biomonitoring and studies of water quality are recommended in view of the projections pointing to the growth of port sector in the western Pará State.
Keywords: Toxicidade; Resíduos de Pesticidas em Alimentos; Peixes; Aracatinga; CNPQ::CIÊNCIAS BIOLÓGICAS::MUTAGENESE; MUTAGÊNESE AMBIENTAL; CIÊNCIAS BIOLÓGICAS